Gaps and Knowledge in the Contemporary Management of Acute Right Ventricular Failure - Manca, Paolo; Nuzzi, Vincenzo; Mulè, Massimiliano; Sciacca, Sergio; Castrichini, Matteo; Schulz, Uwe; Pereira, Naveen; Thiele, Holger; Jentzer, Jacob; Cipriani, Manlio (Circulation. Heart failure, 2025)
Acute right ventricular failure (ARVF) is commonly seen in the intensive care unit and constitutes a significant clinical challenge, with associated high in-hospital mortality. Recently, the treatment of ARVF has significantly changed, with the progressive implementation of mechanical circulatory support devices that now represent important tools for clinicians in treating this condition. However, despite recent advancements, the optimal approach for ARVF remains elusive, and precise treatment algorithms and comprehensive management protocols are still lacking. In the present review, we explore the pathophysiology of ARVF, highlighting the different mechanisms that may lead to this clinical entity and emphasizing the left and right heart’s complex interplay. We analyze the different therapeutic options that are now available for short- and long-term management of ARVF, with a particular focus on the advantages and disadvantages of the mechanical circulatory support devices actually used. Furthermore, we propose future directions in the field and a possible flowchart for the treatment of this condition.